Inclusive and exclusive beneficiary attributions: The role of social identity complexity in interpretations of and punishment for dissent. (September 2022) - Roccas, Sonia; Amit, Adi; Oppenheim-Weller, Shani; Hazan, Osnat; Sagiv, Lilach
We suggest that intentionality attributed to dissenting behavior in intergroup contexts (e.g., exposing one's country's secrets) may be conceptualized as benefitting one of four social circles. Two social circles exclude the perceiver: (a) the actor him/herself and (b) the outgroup affected by the behavior; and two circles include the perceiver: (c) the ingroup of both the perceiver and the actor and (d) humanity as the ultimate collective including both ingroup and outgroup. We further suggest that adopting different beneficiary attributions depends on the perceivers' social identity complexity (Roccas & Brewer, 2002), which refers to an individual's representation of their multiple social identities on a continuum from highly overlapping to highly differentiated (i.e., simple vs. complex social identity). Perceivers are more likely to attribute dissent behavior to social circles that exclude (rather than include) themselves the simpler their social identity; such exclusive attributions lead to harsher moral judgements, expressed as punitiveness.